1977
DOI: 10.1073/pnas.74.6.2480
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface-associated structural proteins in connective tissue cells.

Abstract: Collagen and/or procollagen was demonstrated on the surface of monolayers of fibroblasts from normal rat kidney by indirect immunofluorescence with affinity-purified antibodies to collagen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(45 citation statements)
references
References 39 publications
5
40
0
Order By: Relevance
“…The mechanism of these two effects is unknown. Fibroblast cultures contain fibrils which stain for both FN and collagen when examined by immunofluorescence microscopy (17). The basis for this congruence of location may be the recently described noncovalent interactions of FN with other FN molecules (44) and with collagen (18).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of these two effects is unknown. Fibroblast cultures contain fibrils which stain for both FN and collagen when examined by immunofluorescence microscopy (17). The basis for this congruence of location may be the recently described noncovalent interactions of FN with other FN molecules (44) and with collagen (18).…”
Section: Discussionmentioning
confidence: 99%
“…While this indicates the cables contained fibronectin, it of course does not mean that fibronectin was their only constituent (9,51,61,68). In submembranous regions of ECM sites, a-actinin labeling was generally present, but vinculin labeling occurred less frequently.…”
Section: Immunolabeling Patterns Of Contact Sitesmentioning
confidence: 99%
“…However, ECM cables such as are involved at these sites most likely contain other fbrous components besides fibronectin, such as glycosaminoglycans (61) and collagen (9,51,68), which may be more directly bound to the external surface of the cell at those sites; the involvement of fibronectin at these ECM-1 sites could therefore be totally indirect (see above, Fig. 9).…”
Section: Localization Of Fibronectinmentioning
confidence: 99%
“…Fibronectin may have provided a template for the proper deposition of GP140 through noncovalent interactions, followed by the intermolecular disulfide bonding of matrix GP140 . A number of reports (4,5,7,(31)(32)(33) have indicated that type I and III collagens and/or procollagens also co-distribute with fibronectin in the extracellular matrix .…”
Section: Assembly Of Gp140 In the Extracellular Matrixmentioning
confidence: 99%